Turnover intention among talented lecturers: A pilot study / Ida Rosnita Ismail … [et al.] - Ismail, Ida Rosnita; Tajuddin, Norulhuda; Mat Yunus, Nor Khairunnisa; Ali, Roslina (2012)
Talent management is an emerging issue in the field of human resources management. Past studies on talent management have shown that organizations are competing for talented employees as an effort in gaining competitive advantage. Thus, retaining talented employees has become an important agenda for human resources management. Our study intends to examine the relationship between turnover intention and its antecedents among talented lecturers. Before pursuing on a large-scale research, we conducted a pilot study on a convenience sample of UiTM Pahang lecturers. The objective of our study is to test the feasibility, reliability, and validity of the turnover intention study. Partial least squares path modeling technique was employed to analyze the data. Findings revealed that most of the measurement criteria evaluations for both reflective and formative constructs were met except indicator reliability and internal consistency reliability. In general, this study shows that there is a need to refine the survey questionnaire by addressing several issues relating to the feasibility, reliability, and validity of the turnover intention study.